2016
DOI: 10.1037/adb0000155
|View full text |Cite
|
Sign up to set email alerts
|

Attempts to stop or reduce daily cannabis use: An intensive natural history study.

Abstract: We attempted to replicate and add to our prior study of attempts to stop or reduce cannabis use among daily cannabis users trying to change on their own, by observing a larger sample and adding further clinically-relevant outcomes. Daily users (n = 193) who intended to stop or reduce sometime in the next 3 months called an Interactive Voice Response system each morning for 3 months to report on cannabis use, attempts to stop or reduce, withdrawal symptoms, etc., on the prior day. This study replicated our prio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(17 citation statements)
references
References 69 publications
(92 reference statements)
1
12
0
Order By: Relevance
“…Waves Study Duration (years) No. Retention Strategies Clinical cohort studies Adolescent and adult non-injecting heroin users [ 32 ] Project Brown 300 16–40 98% 2 1.00 9 Adolescent/young adult cancer patients [ 33 ] Resilience in Adolescents and Young Adults with Cancer Study 52 17.6 35% 3 1.50 4 Adolescent/Young Adult mobile young injection drug users [ 34 ] 101 22 48% 6 2.00 9 Adolescents and young adults with Type 1 Diabetes [ 35 ] Young Adult Diabetes Assessment (YADA) 204 17–18 97% 3 5.00 18 Adult asthmatic pregnant women [ 36 ] Syracuse AUDIT (Assessment of Urban Dwellings for Indoor Toxics) 103 25.4 86% 5 1.00 9 Adult cannabis users [ 37 ] 193 32 84% 90 0.25 3 Adult entitlement claimants from the Accident Compensation Corporation [ 38 ] Prospective Outcomes of Injury Study (POIS) 2856 18–64 79% 4 2.00 4 Adult major trauma patients [ 39 ] Victorian State Trauma Registry 1102 40 70% 2 0.50 <...>…”
Section: Resultsmentioning
confidence: 99%
“…Waves Study Duration (years) No. Retention Strategies Clinical cohort studies Adolescent and adult non-injecting heroin users [ 32 ] Project Brown 300 16–40 98% 2 1.00 9 Adolescent/young adult cancer patients [ 33 ] Resilience in Adolescents and Young Adults with Cancer Study 52 17.6 35% 3 1.50 4 Adolescent/Young Adult mobile young injection drug users [ 34 ] 101 22 48% 6 2.00 9 Adolescents and young adults with Type 1 Diabetes [ 35 ] Young Adult Diabetes Assessment (YADA) 204 17–18 97% 3 5.00 18 Adult asthmatic pregnant women [ 36 ] Syracuse AUDIT (Assessment of Urban Dwellings for Indoor Toxics) 103 25.4 86% 5 1.00 9 Adult cannabis users [ 37 ] 193 32 84% 90 0.25 3 Adult entitlement claimants from the Accident Compensation Corporation [ 38 ] Prospective Outcomes of Injury Study (POIS) 2856 18–64 79% 4 2.00 4 Adult major trauma patients [ 39 ] Victorian State Trauma Registry 1102 40 70% 2 0.50 <...>…”
Section: Resultsmentioning
confidence: 99%
“…While abstinence is the most common primary outcome for CUD intervention trials, reduction in use is frequently reported as a primary or secondary outcome in CUD interventions, and reduction attempts are more common among cannabis users attempting to change cannabis use patterns (Hughes et al, 2016). The majority of trials included in the current review reported an outcome measuring reduction in frequency and quantity of use, and nearly 50% of trials included reduction as a primary outcome.…”
Section: Challenges In Assessing Reduction In Cannabis Usementioning
confidence: 97%
“…Most heavy cannabis users interested in changing their use, are unsuccessful when left to their own devices (Hughes et al, 2016). Evidence-based psychotherapies have been studied to treat CUD, and various approaches have been shown to have clinical utility (Budney et al, 2000;Budney et al, 2006;Copeland et al, 2001).…”
Section: Introductionmentioning
confidence: 99%